2016
DOI: 10.1038/srep29260
|View full text |Cite
|
Sign up to set email alerts
|

Evolution equation for quantum coherence

Abstract: The estimation of the decoherence process of an open quantum system is of both theoretical significance and experimental appealing. Practically, the decoherence can be easily estimated if the coherence evolution satisfies some simple relations. We introduce a framework for studying evolution equation of coherence. Based on this framework, we prove a simple factorization relation (FR) for the l1 norm of coherence, and identified the sets of quantum channels for which this FR holds. By using this FR, we further … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 63 publications
0
74
0
Order By: Relevance
“…and for E F above E A and E M , (5) indicates that the beating pattern forms only when the Fermi energy E F is between E M and E A . Here, the beating pattern arises because of the topological nature of the semimetal, different from the Zeeman splitting [39,40,65], nested Fermi surfaces [34], and orbital quantum interference [66].…”
Section: Refmentioning
confidence: 99%
“…and for E F above E A and E M , (5) indicates that the beating pattern forms only when the Fermi energy E F is between E M and E A . Here, the beating pattern arises because of the topological nature of the semimetal, different from the Zeeman splitting [39,40,65], nested Fermi surfaces [34], and orbital quantum interference [66].…”
Section: Refmentioning
confidence: 99%
“…On the other hand, compared with quantum correlation, quantum coherence is another basic notion in quantum theory and has witnessed an on‐going interest in pursuing the relevant quantification in recent years . It derives from the quantum state superposition principle, and is regarded as a physical resource in optics experiments and various quantum technologies, such as quantum thermodynamics, quantum sensing and metrology, and quantum biological systems .…”
Section: Introductionmentioning
confidence: 99%
“…The answer to the second question is in the affirmative. There are, indeed, two recent articles by Hu and Fan [1,2] dealing with 3-dimensional Gell-Mann channels. They are defined with the use of the Kraus operators, and then it is assumed that their eigenvectors are the Gell-Mann matrices.…”
Section: Two Channelsmentioning
confidence: 99%
“…For the Gell-Mann channel given by its eigenvalue equations, we found its time-local generator together with the conditions under which this generator has the corresponding GKSL form. The EV Gell-Mann channels can be used in the theory of quantum coherences and quantum correlation measures [1,2]. It was shown that, under certain circumstances, the evolution equations of coherences and correlation measures obey the factorization relation.…”
Section: Applications and Final Thoughtsmentioning
confidence: 99%